ONLINE SOCIAL NETWORKS THREATS EXPERIENCED BY GIRLS ATTENDING A CHILD DAY CARE CENTRE - SKALIŠIENĖ, Rasa (Socialinė teorija, empirija, politika ir praktika, 2015)
The article analyses the problem of threats experienced on online social networks by girls attending a Child Day Care Centre. In order to reveal what actions carried out by girls on online social networks pose a threat to them, a qualitative study of 20 girls from four Lithuanian Child Day Care Centres was conducted using the focus group method. The results revealed that majority of the girls from the risk group face the following threats to their security: publicizing personal information and sharing it with strangers; communication with strangers online and meeting with them outside the Internet; negative actions of Internet users. The study found that the girls from the risk group fail to recognize the threats of online social networks and do not realize their consequences, and their need to protect themselves in cyberspace is quite weak.